Orthographic standardization in middle english documentary texts. - Esteban-Segura, María Laura (Universidad de Murcia, 2022)
Standardisation has been defined as “the reduction of variation in language, or […] as the selection, elaboration and codification of a particular dialect” (Hope, 2000: 51). When language users are unconsciously sensitive to linguistic variation, natural processes of competition are triggered; these “operate independently for each linguistic variable, producing the hybrid features of Standard English” (Hope, 2000: 52). The term ‘Standard English’ is commonly used in sociolinguistics “to denote the primarily written, especially printed, usage of educated people” (Leith and Graddol, 2007: 83). The focus of this paper is on written usage, but that found in manuscript, rather than print, form. The reason for choosing handwritten texts as the object of study has to do with the fact that the origin of Standard English can be traced back to the fourteenth and fifteenth centuries, when manuscripts were the main vehicle for the written word, because “specific changes in writing practices are identifiable in those centuries” (Wright, 2020: 4). It has been argued that the early stage of standardisation is characterised by the reduction of grammatical and orthographical variants (Wright, 2020: 13). Therefore, the present paper evaluates the level of orthographic standardisation in Middle English documentary texts by assessing the competition of old and new spellings. For the purpose, the occurrence and use of the pair forms <þ>/, / and <ȝ>/ are investigated in a specific text-type. The source of evidence comes from A Corpus of Middle English Local Documents (MELD), version 2017.1 (Stenroos, Thengs and Bergstrøm, 2017-), which comprises transcriptions of 2,017 English documentary writings from the period 1399-1525. The corpus consists of administrative texts and letters from different urban centres, which allow to analyse the supralocal spread of the spellings under consideration as well as the adoption of orthographic innovations in this type of writing.
Keywords: Lingüística histórica; Inglés - Normalización - (10..-14..); Lengua estándar; Ortografía - Normalización; Inglés medieval - Textos; Inglés medio - Manuscritos; Inglés - Ortografía - Obras anteriores a 1500; Corpus lingüístico; Standarization; Middle english; Documentary texts; Spelling